Đặc điểm hình thế thời tiết gây mưa, lũ, lụt lớn ở các tỉnh Thanh Hóa, Nghệ An, Hà Tĩnh thời kỳ 1997-2001 - Vân, Nguyễn Khanh; Tăng, Bùi Minh (Vietnam Journal of Earth Sciences, 2004)
The characteristics of synoptic situations causing very heavy rains and serious inundation, floods in Thanh Hoa, Nghe An, Ha Tinh provinces